Chemical partitioning for the Co–Pr system: First-principles, experiments and energetic calculations to investigate the hard magnetic phase. (15th January 2016) - Zhou, S.H.; Kramer, M.J.; Meng, F.Q.; McCallum, R.W.; Ott, R.T.
Abstract: Co5 Pr-D2d is promising permanent magnet. Due to its peritectic formation feature, there is a synthetic challenge to produce single Co5 Pr-D2d phase. The object of this study is to assess thermodynamic pathways for crystalline phases under far-from-equilibrium conditions by combining first-principles calculations and experimental measurements into a robust description of the thermodynamic behavior. With the energetic calculations, temperature and time dependent phase selections are predicted under varying degrees of chemical partitioning. Our calculation to assess the chemical partitioning-temperatures indicates that the major magnetic compounds: Co17 Pr2 -α, Co5 Pr-D2d, Co19 Pr5 -β, and Co7 Pr2 -χ form from a congruent manner to eutectic reactions with decreasing cooling rate. The compositions of the compounds from these highly driven liquids can be far from equilibrium. Graphical abstract: Highlights: Chemical partitioning calculation based on energetics is powerful tool for materials design. Single phase, eutectic, and peritecitc microstructures can be accessed by controlling the chemical partitioning. The magnetic properties can be tailored through controlling the microstructures.